PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD BERBASIS KAHOOT UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PESERTA DIDIK SD NEGERI NGEBEL - Damar Wiyati; Henry Aditia Rigianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this project is to create Kahoot-based flashcard learning materials and assess their viability, usefulness, and efficacy in raising third-grade primary school pupils' reading proficiency. Since reading is the basis for comprehending a variety of learning materials, it is an essential skill that students must acquire at the primary school level. In reality, though, a lot of pupils still struggle with reading, which highlights the necessity for interesting educational materials that fit students' personalities. A Research and Development (R&D) technique including many stages—needs analysis, product design, product development, expert validation, restricted trials, product modification, and field testing—was used in this study. Third-grade primary school pupils who were split into an experimental class and a control class served as the research participants. Pretests and posttests of reading proficiency were used to gauge efficacy, student and teacher response questionnaires were used to gauge practicality, and validation questionnaires from media and material specialists were used to ascertain media feasibility. While efficacy data were evaluated utilizing precondition tests, such as normality and homogeneity tests, followed by an Independent Sample t-test, feasibility and practicality data were studied descriptively. Based on assessments by media and material specialists, the results show that the Kahoot-based flashcard medium is viable. Responses from both teachers and students demonstrate the usefulness of the media in the classroom. Additionally, reading proficiency in the experimental and control groups differs significantly, according to efficacy testing. As a result, Kahoot-based flashcard materials are useful for raising third-grade primary school pupils' reading proficiency.